Oceanographic Data of the 38th Japanese Antarctic Research Expedition from November 1996 to March 1997 - オイカワ, コウシロウ; イワモト, コウジ; OIKAWA, Koushiro; IWAMOTO, Koji (National Institute of Polar Research, 1999)
P(論文) The results of oceanographic observations on board the icebreaker "Shirase" and tidal observations at Syowa Station, Antarctica, are presented in this report. The oceanographic observations were carried out by the summer party of the 38th Japanese Antarctic Research Expedition (JARE-38) during the austral summer of 1996/1997. The tidal observations were carried out by the winter party of JARE-37 from February 1996 to January 1997. departmental bulletin paper